A Euro area stock market model with betas dependent on the financial markets cycle. (24th March 2014) - Fonseca, José Soares Da
This paper estimates market models for the Euro area stock markets of France, Germany, Holland, Italy and Spain, with beta parameters dependent on the financial cycle phases. These models support the calculation of time–varying Treynor ratios, which compare the performance of these domestic markets across different phases of the financial cycle in the Euro area stock markets.